Colorimetric Determination of Magnesium in Blood and Saliva in Oral Squamous Cell Carcinoma and Potentially Malignant Disorders by Titan Yellow Method - Bagulkar, Bhupesh Bhayyaji; Chaudhary, Minal; Gawande, Madhuri; Patil, Swati; Gadbail, Amol; Bagulkar, Smita (Journal of Orofacial Research, 2013)
Background: The purpose of this study to evaluate and compare the magnesium concentration in blood plasma and saliva of oral squamous cell carcinoma, potentially malignant disorders and health subjects to serve as a positive marker or indicator in the process of carcinogenesis. Materials and methods: The study consisted of 30 cases each of oral squamous cell carcinoma, potentially malignant disorders and healthy subjects of age and sex matched. The estimation of magnesium in blood plasma and saliva was carried out by colorimeter by using titan yellow method. Results: There was significantly low concentration of magnesium in blood plasma of oral squamous cell carcinoma was noted as compared to potentially malignant disorders (p = 0.000) and healthy subjects (p = 0.000). However, there was no significant difference in magnesium concentration between potentially malignant disorders and healthy subjects. Conclusion: The magnesium concentration was low in both blood plasma and saliva of oral squamous cell carcinoma as compared to potentially malignant disorders and healthy subjects. Thus the magnesium concentration in blood plasma and saliva could be considered as tumor marker, playing an important role in carcinogenesis. Future studies should be carried out for further clarification.